AN EMPIRICAL STUDY ON DETERMINANTS OF CUSTOMER SATISFACTION AND ATTITUDE IN ORGANIZED RETAIL OUTLETS (International Journal of Food and Nutritional Sciences, 2022)
The importance of happy customers in shaping consumers' future spending habits is well-established. Customers who are pleased with the services they get are more inclined to spread the word about their good experiences to others.. The main aims of the study are to outline socio-economic nature of the respondents and to identify the various determinants of Customer Satisfaction. Descriptive research is the method used in this study. Convenient sampling techniques are used to get the main data. i.e., 200 Customers make up the population from whom the data is gathered. Here, the responses are treated as a unit, and analysis is based on consumer feedback provided through a specially designed questionnaire. The core data is gathered via a well-structured, prestigious questionnaire.(Google form).The retail industry has seen dramatic transformations in recent years, both as a consumer activity and a retailing practice. It's one of the biggest and most varied markets in the world. As with any developing market, competition is fierce in India's budding retail sector.